Hydrogen Sulfide and Gut Microbiota: Their Synergistic Role in Modulating Sirtuin Activity and Potential Therapeutic Implications for Neurodegenerative Diseases - Constantin Munteanu; Gelu Onose; Mădălina Poștaru; Marius Turnea; Mariana Rotariu; Anca Irina Galaction (MDPI AG, 2024)
The intricate relationship between hydrogen sulfide (H2S), gut microbiota, and sirtuins (SIRTs) can be seen as a paradigm axis in maintaining cellular homeostasis, modulating oxidative stress, and promoting mitochondrial health, which together play a pivotal role in aging and neurodegenerative diseases. H2S, a gasotransmitter synthesized endogenously and by specific gut microbiota, acts as a potent modulator of mitochondrial function and oxidative stress, protecting against cellular damage. Through sulfate-reducing bacteria, gut microbiota influences systemic H2S levels, creating a link between gut health and metabolic processes. Dysbiosis, or an imbalance in microbial populations, can alter H2S production, impair mitochondrial function, increase oxidative stress, and heighten inflammation, all contributing factors in neurodegenerative diseases such as Alzheimer's and Parkinson's. Sirtuins, particularly SIRT1 and SIRT3, are NAD+-dependent deacetylases that regulate mitochondrial biogenesis, antioxidant defense, and inflammation. H2S enhances sirtuin activity through post-translational modifications, such as sulfhydration, which activate sirtuin pathways essential for mitigating oxidative damage, reducing inflammation, and promoting cellular longevity. SIRT1, for example, deacetylates NF-κB, reducing pro-inflammatory cytokine expression, while SIRT3 modulates key mitochondrial enzymes to improve energy metabolism and detoxify reactive oxygen species (ROS). This synergy between H2S and sirtuins is profoundly influenced by the gut microbiota, which modulates systemic H2S levels and, in turn, impacts sirtuin activation. The gut microbiota-H2S-sirtuin axis is also essential in regulating neuroinflammation, which plays a central role in the pathogenesis of neurodegenerative diseases. Pharmacological interventions, including H2S donors and sirtuin-activating compounds (STACs), promise to improve these pathways synergistically, providing a novel therapeutic approach for neurodegenerative conditions. This suggests that maintaining gut microbiota diversity and promoting optimal H2S levels can have far-reaching effects on brain health.